“Conservative Enlightenment” as “Heroisation of the Present” - Boris V. Mezhuev (Кантовский сборник, 2023)
This text is a polemic against the 2023 article by Sergey N. Gradirovsky who wrote about the present-day relevance of Immanuel Kant’s concept of enlightenment and challenged the idea of the modern human being as a child who needs an external guardian or guide to control his behaviour. In my polemic with Gradirovksy I point out that in addition to “self-incurred immaturity” Kant writes about the historical “immaturity” of savage or backward peoples. I also argue that for Kant “maturity” carries not only biological but also socio-historical connotations. I show that in the modern world Kant’s idea of the social or even historical maturity of the modern human acquires serious problematisation which was shown to be possible and inevitable in the article “What Is Enlightenment?” (1784) and its notion of the historicity of enlightenment, i.e. the very strategy of modernity is possible only when humankind reaches a certain historical age. Using as a point of departure the ideas of the French philosopher Michel Foucault, I maintain that the Kantian conception of enlightenment is at once ironic and tragic. It is ironic because it does not rule out that its main thesis on the historical maturity of the human being may turn out to be wrong. It is tragic because its main thrust is “heroisation of the present”, i.e. a readiness to resist the temptation of being absorbed by the future, which takes on added relevance in view of the virtualisation of reality.